PENGARUH COSTUMER EXPERIENCE TERHADAP WORD OF MOUTH YANG DIMEDIASI OLEH COSTUMER SATISFACTION: STUDY PADA KONSUMEN BANK SYARIAH MANDIRI CAB JOMBANG - Purwanto, Nuri (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
customer experience marketing is important to learn because changes in the behavior of customers who do not only see the product or service not only from service or from the quality of the product or service but more than that, namely experience, the experience must be unforgettable and positive. This study aims to predict the effect of customer experience on word of mouth either directly or indirectly using a mediating variable, namely customer satisfaction, this study uses an instrument, namely a questionnaire distributed to 100 customers of Bank Mandiri Syariah Jombang. and the results of the study show that the variable customer experience has a direct and indirect effect on word of mouth through customer satisfaction, and the variable costumer satisfaction directly affects word of mouth